Welcome to the Microscopy Today Buyers' Guide. (11th March 2014) - Unknown
Abstract : The guide is published in print and online atwww.microscopy-today.com . For such a guide to be truly useful, it must be comprehensive. Thus, the editors have assembled an index identifying hundreds of products listed under more than 300 categories.